'So we beat on, boats against the current, borne back ceaselessly into the past': legacy, care leavers and university study. (7th February 2022) - Simpson, Donald; Murphy, Seán F.
ABSTRACT: International research reveals underrepresentation and problems of retention, amongst care leavers in higher education, are universal. Drawing upon qualitative research in England, we highlight legacy as an under-explored and double-edged feature of care leavers' motivations to enter and persist in university study. While restricting access to the propulsive power of material resources, in the context of a widening participation policy mandate, our interviewees' care experiences also shaped an 'orientation framework' providing a strong desire to 'prove people wrong' through study. Supporting this orientation were examples of significant other relations; but interviewees' linked lives also meant the past could resurface in the present, resulting in strong emotional reactions. These could threaten orientation to university study by undermining self-reliance and fragile mental health. As the problem of care leavers' retention occurs across different higher education systems with varied structural and cultural specifics, it appears to transcend such issues. We conclude further study of the nuanced issue of legacy may help better elucidate the problem of retention and we advocate for 'corporate parenting' moving beyond an objective list approach to well-being.